Evaluación de la producción in vitro de embriones de alpaca (vicugna pacos) en el laboratorio de biotecnología de la reproducción de la Universidad Técnica de Cotopaxi - Sarzosa Troya, Mario Santiago (2014)
In-vitro Embryo Production is a biotechnology of reproduction which in the last decade has been very significant. This is presented as an alternative of great productive importance, with which it can get to produce offspring of great genetic value from females who could not afford them in other ways. The first chapter of the research indicates the anatomical and physiological aspects of alpacas as well as the characteristics of the technique of In-vitro Embryo Production. This trial was performed in order to determine the percentage of fertilization of the oocytes obtained, determine the amount of recovered embryos, and evaluate the quality of embryos recovered and the evaluation of the technique In-vitro Embryo Production that was developed....